EFFECT OF ORAL IRON TABLET ADMINISTRATION ON SERUM FERITIN AND HEMOGLOBIN CONCENTRATION OF PRE-PREGNANT WOMEN WITH MILD IRON DEFICIENCY ANEMIA IN BALI - Seri Ani, Luh; Bakta, I Made; Suryadhi, INT; Agus Bagiada, IN (Udayana University, 2007)
Iron deficiency anemia (IDA) is still to be a problem of pregnant women healthrelated to its high prevalence and its negative effects on health. Prevention efforts by ironsuplementation in pregnant woman have not reducing IDA problem in pregnant women yet. This failure is probably due to the assumption that IDA have been seen pre-pregnant. Totest this hypothesis, a quasi experimental study was conducted by randomized pre and posttest control group design. Sample were collected by multistage sampling random technicconsist of 47 women in treated group and 52 in control group. Both group were serumferritin and hemoglobin value test untill 3 time, pre-pregnant, early pregnant and duringpregnant. Iron tablet was administrated to treated group from the beginning of pre-pregnantperiod, continued until the first 3 months of pregnancy, while in control group iron tabletwas only given during the first 3 months of pregnancy. T-group result shown that meanserum ferritin and hemoglobin concentration at pregnant women on treated group(33,45±14,12 ?g/dL dan 12,25±1,20 g/dl) more high than control group (19,65±8,99 ?g/dLdan 10,91±0,67 g/dl), p<0,05. Mean difference serum ferritin and hemoglobinconcentration at pregnant women is 13,8 ?g/dL dan 1,34 g/dl (p<0,05). Benefid analysisresult shown that iron suplementation since pre-pregnant more benefid than ironsuplementation during pregnant (BCR >1). Based on these results, it can be concluded thatiron supplementation to IDA women starting from pre-pregnant period results in a bettereffect compare to oral iron supplementation during pregnancy only.